Molecular modeling of the interaction of the dihydroquercetin and its metabolites with cyclooxygenase-2 - R. P. Terekhov; I. A. Selivanova (Бюллетень сибирской медицины, 2019)
Background. Dihydroquercetin (DHQ) is a natural flavonoid. It has a wide range of pharmacological effects, which includes anti-inflammatory activity. There is a gap in our knowledge about the biochemical mechanisms of the therapeutic potency implementation of this compound. This fact slows down the process of the drug development using DHQ. Molecular modeling is designed to further translate the research from the fundamental experimentation to the real clinical practice. Purpose. The study objective was to estimate DHQ as a cyclooxygenase-2 (COX-2) inhibitor by using in silico analysis.Materials and methods. The information about the COX-2 structure was obtained from the Protein Data Bank (code 5KIR). The 3D-models of DHQ were generated by using the ChemBioDraw Ultra software. Docking was carried out in the GOLD program after the corresponding validation of molecular modeling algorithms based on experimental data of X-ray diffraction analysis.Results. The design of this study is based on the rational selecting of the virtual ligand structures. It gives an opportunity to optimize the quantum-mechanical calculation. By using in silico analysis, it was shown that DHQ and some of its metabolites demonstrate ability of binding to SER353, SER530, and ARG513 of COX-2 at the catalytic site.Conclusion. Important α-amino acids for intermolecular interaction of DHQ and its metabolites with COX-2 were determined during this study. Our data can be used for the development of new antiinflammatory drugs on the base of DHQ.